COMPARISON OF POSITIVE BACTERIAL CULTURE RATE FROM URINE SPECIMEN AND CATHETER SWAB IN INDWELLING CATHETER PATIENTS - Yusuf, Marzuki; Alif, Sabilal; Soebadi, Doddy M; Debora, Kartuti; P, Widodo J (Indonesian Journal of Urology, 2010)
Objective: The study aims to study the difference between urinary culture before and after indwelling catheter insertion and also the difference in positive bacterial culture rate between urine and catheter swab at the 7th and 14th days. Material & method: The subject of this study were patients who used indwelling catheters in urology outpatient department. The sample was allocated into two groups of 10 patients each, 7 and 14 days group. Sterile urinary culture was initially checked before catheter insertion. After 7 and 14 days of catheterisation respectively, urine and intraluminal catheter swab were performed upon removal. All samples were examined in Microbiology Department using McConkey and Nutrient agar (Mayo technique – T/T33). After 24 hours incubation, bacterial colonies were identified. Results: All urinary cultures obtained before the study were sterile, after 7 days catheter insertion two cultures (20%) remained negative and the remainder (80%) became positive. McNemar test result was 0,008 (p<0,05). In 14 days group after catheter insertion only one (10%) remained negative while 9 others were positive for bacteria. Mcnemar test shows 0,004 (p<0,05). The urinary and catheter swab culture is not significantly different in 7 days of indwelling catheterization patients (0,500; p>0,05) and also in 14 days patients (1,000, p>0,005). While the catheter swab culture is significantly positive after administering the urinary catheter in 7 and 14 days of catheterization (0,002; p<0,05). Conclusion: There was significant difference in urinary culture positive rate before and after catheter insertion in 7th and 14th day. Bacteriuria rose sharply after urinary catheter insertion despite aseptic procedure. There was no difference in culture positive rate between urine and catheter swab at 7th day as well as 14th day.